Improving the Regional Revenue: Analyzing the Potential of Tax Collection - Muhammad Istiyansyah Ulman Idris; Annisa Paramaswary Aslam; Kartini Hanafi (Hasanuddin Economics and Business Review, 2023)
Goal of this study is to analyze the potential of restaurant tax and to determine the obstacles and efforts made by the regional government in exploring the potential of restaurant tax in Makassar. This study uses several variables to calculate the potential, effectiveness, and contribution of restaurant taxes. These are, the number of restaurants, average visitors, average food prices, number of days in a year, total regional revenue and restaurant tax rates. The research method used is descriptive qualitative and the results show the potential for restaurant tax is large, not comparable to the realization of tax revenue. This comparative measure is reflected in the effectiveness of restaurant taxes, which value no more than 100% annually. This study proof that the potential for restaurant tax in the city of Makassar has not been optimally used due to socialization and government regulations that have not been implemented properly.Â